The Relationship Between Environmental Knowledge and Environmental Hygiene Participation in Housewives in Sukatani Village, Tapos District, Depok City - Kawita Iga Abrila; Moh. Balya Ali Syaban; Fadiarman Fadiarman (Dinasti Publisher, 2024)
Housewives' participation in environmental hygiene can be one of the solutions to tackle waste. In fact, if all housewives actively participate in environmental hygiene. This type of research uses a correlation research method with a survey approach. In this case, the use of a correlation research method with a survey approach aims to determine the relationship between environmental knowledge and environmental hygiene participation in housewives of Sukatani Village, Tapos District, Depok City. The sample of this study was 92 respondents with respondents, namely housewives in Sukatani Village with a sampling technique with random sampling (randomly). Data collection using questionnaire sheets, interviews, observations. The data that has been collected is analyzed using simple regression analysis to see the relationship between two variables through normality test, linearity test. From the results of data analysis, there is a relationship between environmental knowledge and environmental hygiene participation in housewives in Sukatani Village, Tapos District, Depok City which is very significant with the correlation results r; 0.688 and f; 80.957 p = 8.998 p <0.05 with the results of the contribution of X to Y of 0.474 x 100 = 47.4% so that there are still variables that can connect with community participation by 52.6%.